1980
DOI: 10.1159/000145194
|View full text |Cite
|
Sign up to set email alerts
|

Light- and electron-microscopic study of the near-term paraplacenta of the domestic cat

Abstract: The entire chorioallantoic paraplacenta of the near-term domestic cat shows cytological evidence of maternal-fetal substance transfer, but there are probably qualitative and quantitative differences and increased transfer progressing from the poles to the placenta! border. In the interfetal polar zone, the cytotrophoblast remains proliferative, is squamous to columnar and shows only a small amount of pinocytotic activity. However, in the adjacent ring of the free polar zone, where the trophoblast is cuboidal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 18 publications
1
14
1
1
Order By: Relevance
“…The process of placental detachment seems to occur suddenly, as the foetuses aborted were alive. This sudden detachment might be the result of a certain ‘destabilization’ of the foetal–maternal connection, probably facilitated through haemorrhage that developed as the result of several ‘leaky’ maternal venules, which could not be observed in the intact pregnant queens of this study and several previous investigations (Leiser and Enders 1980a,b; Leiser and Koob 1993).…”
Section: Discussioncontrasting
confidence: 65%
“…The process of placental detachment seems to occur suddenly, as the foetuses aborted were alive. This sudden detachment might be the result of a certain ‘destabilization’ of the foetal–maternal connection, probably facilitated through haemorrhage that developed as the result of several ‘leaky’ maternal venules, which could not be observed in the intact pregnant queens of this study and several previous investigations (Leiser and Enders 1980a,b; Leiser and Koob 1993).…”
Section: Discussioncontrasting
confidence: 65%
“…1979, 1984; Myagkaya and De Bruijn 1982; Santos et al. 1996), carnivores (Wislocki and Dempsey 1946; Gulamhusein and Beck 1975; Leiser and Enders 1980; Dumartin and Canivenc 1991) and insectivores (King et al. 1978).…”
Section: Discussionmentioning
confidence: 99%
“…It is frequently suggested that the haemophagous areas or ‘placental hematomes’ contribute to iron transfer from mother to foetus, based on studies using light and transmission electron microscopy, immunohistochemistry and electron immunomicroscopy with markers of iron transport, X‐ray microanalysis and injection of Fe 59 into the maternal circulation (Hoyes 1972; Burton et al. 1976; Leiser and Enders 1980; Myagkaya and De Bruijn 1982; Murai and Yamauchi 1986; Latshaw 1987; Santos et al. 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructural studies of uptake and subsequent degradation of maternal erythrocytes have been made in the cat (Malassin~ 1977(Malassin~ , 1982Leiser and Enders 1980), sheep (Burton et al 1976;Myagkaya and Vreeling-Sindelarova 1976;Myagkaya etal. 1979;Myagkaya and Schellens 1981), shrew (King et al 1978) and seals (Sinha and Erikson 1974).…”
Section: Introductionmentioning
confidence: 99%